Pengaruh Kompetensi dan Pengembangan Karir Terhadap Loyalitas Karyawan di PT. Moratas Guna Abadi Bogor - Neneng Fadilah; Sari Marliani; July Yuliawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The purpose of this study is to determine how competence and career development impact employee loyalty at PT. Moratas Guna Abadi Bogor. The phenomenon underlying this study is the indication of low loyalty, lack of initiative, and obstacles in employee career development. This study was conducted using quantitative descriptive and verification techniques. This study involved 300 employees, and 75 samples were taken with the Slovin formula using multiple linear regression. and hypothesis testing through t-test and F-test with SPSS. The results of descriptive and verification studies show that competence gets an average value of 250.4 in the scale range of 195-255 in the fairly good category, career development gets an average value of 247.3 in the scale range of 195-255, employee loyalty gets an average value of 238.2 in the scale range of 195-255. The study shows that, partially, the competency variable has no effect on employee loyalty, with a significance value of 0.394 > 0.05 and a calculated t-value of 0.857 < 1.993. Career development has a positive and significant effect on employee loyalty, with a significance value of 0.000 < 0.05 and a calculated t-value of 5.220 > t-table of 1.993. Simultaneously, competency and career development significantly influence employee loyalty, with a significance value of 0.000 < 0.05 and a calculated F-value of 32.922 > F-table of 3.122. The coefficient of determination (R2) of 0.478 indicates that the competency and career development variables contribute 47.8% to explaining employee loyalty.